Predictive Value of Endometrial Thickness in Detecting Endometrial Malignancy in Patients with Postmenopausal Bleeding - Onur Kaya; Cem Dane; Ecem Kaya; Mehmet Murat Semiz; Ahmet Çetin; Gamze Saygı (Haseki Tıp Bülteni, 2014)
Aim: The aim of this study was to investigate the place of endometrial thickness in detecting endometrial malignancy in patients with postmenopausal vaginal bleeding. Methods: In this study, we retrospectively evaluated hospital records of 380 patients who had undergone endometrial biopsy with the diagnosis of postmenopausal bleeding in the Department of Obstetrics and Gynecology at Haseki Training and Research Hospital between January 2008 and January 2012. Results: Analysis of the biopsy specimens revealed benign or premalignant endometrium in 355 of the 380 patients who were histopathologically diagnosed with postmenopausal bleeding. The mean endometrial thickness in 25 patient with malign endometrium was 11.6±8.2 mm. In our study, when a endometrial thickness cut-off value of 10.8 mm was taken, the sensitivity, specificity, and negative predictive value was found to be 84%, 52%, and 96%, respectively. Conclusion: In our study, almost all patients (96%) with endometrial thickness of less than 10.8 mm, were free from endometrial malignancy. (The Medical Bulletin of Haseki 2014; 52:164-7)